The Use of Computerized Educational Instruction in Iraqi Secondary Schools from Teachers' Viewpoints - Alabbad, Arafat AbdAli Rakhees (Arab Journal for Sciences and Research Publishing, 2016)
The Purpose of the Study is to investigate teachers' opinions regarding the benefits of computerized educational instruction. It also shows the barriers which hinder the use of computerized educational instruction in Iraqi secondary schools. Methodology: This study is pedagogical. The study sample includes (100) Iraqi teachers who are randomly chosen from different secondary schools in the center of Basra city. The researcher uses a questionnaire as a tool to collect data. The questionnaire given consists of two fields: the first field is about the advantages of computerized educational instruction while the second concerns the obstacles to the use of computerized educational instruction in Iraqi secondary schools. Thus, a questionnaire of (28) items, divided into two fields, has been distributed to the participants. For data entry and analysis, the researcher uses the Weighted Mean, (W.M.), Percentile Weight, (P.W.) and Spearman-Brown formula. Results: Concerning the benefits of using computerized educational instruction, item no.(14): "computer prepares students for living in an electronic environment" scores the highest P.W. (91%). Item no.(8): "computerized educational instruction stimulates students to practice different educational activities" comes next with P.W. (90%). Regarding the barriers which hinder the use of computerized educational instruction in Iraqi secondary schools, Item no.(19): ''the lack of training courses on the use of computer for both teachers and students'' comes first with P.W. (95%). Item no.(27): ''the insufficiency of computers in secondary schools compared with the large number of students in each classroom'' gets P.W. (94%). Conclusion: Most Iraqi teachers believe that the use of computerized educational instruction would be of assistance to students affecting their learning and increasing their enjoyment. Also, they think that the lack of teachers and students' training besides the lack of computers in most schools are the main impediments to the use of computerized educational instruction in Iraqi secondary schools.
Keywords: Computerized Instruction; Benefits; Barriers; Disadvantages; Teachers